Overcoming Infrastructure Challenges to Unlock Food Security in Rural Indonesia: Mengatasi Tantangan Infrastruktur untuk Membuka Ketahanan Pangan di Pedesaan Indonesia - Arifin, Muhammad Zainul; Sukmana, Hendra (Indonesian Journal of Public Policy Review, 2024)
General Background: Food security is a critical issue in rural areas, especially in developing countries, where sustainable agricultural practices and government support play a vital role in ensuring a stable food supply. Specific Background: In Sumorame Village, Candi District, Sidoarjo Regency, the local government has implemented a food security program aimed at improving agricultural productivity and community welfare. Knowledge Gap: Despite the program's significance, little is known about the specific factors influencing its success, particularly in the context of rural governance and local agricultural conditions. Aims: This study aims to describe and analyze the implementation of the food security program in Sumorame Village, focusing on four key factors: communication, resources, disposition, and bureaucratic structure. Results: The findings reveal that communication between the village government, farmers, and community groups has been effective through targeted socialization efforts. Human resources are competent, with strong collaboration among farmer groups. Financial resources have been allocated in accordance with regulations, but physical infrastructure remains inadequate due to limited agricultural land, unfavorable geographical conditions, and suboptimal hydroponic yields. Disposition among stakeholders is positive, with high commitment observed. The bureaucratic structure has been functioning in accordance with established Standard Operating Procedures (SOPs). Novelty: This study highlights the importance of resource optimization, particularly in agricultural infrastructure, and stresses the need for improved technological integration to enhance program outcomes. Implications: The results suggest that strengthening communication and addressing physical resource limitations are crucial for improving food security program effectiveness in rural areas. This study provides valuable insights for policymakers seeking to enhance rural food security initiatives. Highlights: Communication is crucial for successful food security program implementation. Infrastructure limitations present significant challenges to agricultural productivity. Collaboration and commitment among stakeholders enhance program effectiveness. Keywords: Food security, rural governance, agricultural infrastructure, communication, resource optimization